The glass transition temperature of iron and titanium containing phosphate based glasses - Shaharuddin, Sharifah Imihezri; Ahmed, I.; Furniss, D.; Parsons, A.J.; Rudd, C.D. (Trans Tech Publications Ltd., Switzerland, 2015)
In this study various compositions in the phosphate based glass (PBG) system of (50-x)P2O5-40Ca- (5+x)Na-5TiO2 and (50-x)P2O5-40Ca-(5+x)Na-5Fe2O3, where x= 5 and 10 were investigated for glass transition temperature (Tg) via thermo mechanical analyser (TMA) and differential scanning calorimetry (DSC). The amorphous nature of the glasses was confirmed via XRD. The Tg measured via DSC was consistently higher by 19°C-29°C compared to TMA and was due to the thermal history and the heating rate of the samples. The Tg increased with increasing phosphate content in both glass systems. The Tg for Ti containing PBG was found to be in the range of 453°C-500°C whilst Tg for Fe containing PBG was in the range of 449°C-494°C. Consistently higher Tg for the Ti containing glass series compared to the Fe containing glasses may be attributed to the smaller ionic radius and therefore higher field strength of Ti4+ .